2018
DOI: 10.1186/s12917-018-1355-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spray and oral delivery of Newcastle disease I2 vaccine in chicken reared by smallholder farmers in central Ethiopia

Abstract: BackgroundNewcastle disease (ND) is a highly infectious disease causing considerable economic losses to poultry farmers worldwide. Conventional vaccine delivery methods are not suitable for smallholder and rural poultry producers, and thus appropriate vaccination methods need to be sought. This study was carried out with the main objective of evaluating the efficacy of ND I2 vaccine delivered via drinking water and spray under smallholder farmers’ condition in Minjar-Shenkora district, central Ethiopia. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…The use of inactivated vaccine against ND in broiler breeder is required and its should be used earlier than point of laying period. Also, for avoidance the loss of egg trait, egg production, hatching and to achieve extreme level of antibodies titer in broiler breeder flocks (19). In this study the titer of antibodies was elevated suddenly and reach to high level 37512±2049.4 at 20-1 week/day of age and this elevation of titer was due to the rolling or circulating of field virus within the flock with on obvious clinical signs (subclinical infection) or may have donated to the fact that existing vaccines and vaccination programs are not maximally efficient in avoiding the transmission of infection (20) and it was described that vaccination campaigns of poultry against ND can only protect the birds from the more severe consequence of highly pathogenic (velogenic) NDV, but not from infection and replication of the virulent strains of virus (21).…”
Section: Discussionmentioning
confidence: 99%
“…The use of inactivated vaccine against ND in broiler breeder is required and its should be used earlier than point of laying period. Also, for avoidance the loss of egg trait, egg production, hatching and to achieve extreme level of antibodies titer in broiler breeder flocks (19). In this study the titer of antibodies was elevated suddenly and reach to high level 37512±2049.4 at 20-1 week/day of age and this elevation of titer was due to the rolling or circulating of field virus within the flock with on obvious clinical signs (subclinical infection) or may have donated to the fact that existing vaccines and vaccination programs are not maximally efficient in avoiding the transmission of infection (20) and it was described that vaccination campaigns of poultry against ND can only protect the birds from the more severe consequence of highly pathogenic (velogenic) NDV, but not from infection and replication of the virulent strains of virus (21).…”
Section: Discussionmentioning
confidence: 99%
“…It can be delivered by the oral route and can be applied by unskilled personnel under field conditions. Several studies confirmed that the V4 vaccine is highly protective when given by conventional routes (Mebrahtu et al, 2018). The thermo-stable-12 vaccine produced by NVI and was kindly granted by pan African veterinary vaccine center (PAVVC).…”
Section: The Prospect Use Of the Thermo-stable Vaccinementioning
confidence: 96%
“…Different in effect of spray and aerosols are caused by the size of droplets, coarse droplets are short-lived whereas fine droplets are long-lived. Vaccination through water can also be used, but give varying results due to the variation in water intake between and among birds (Mebrahtu et al, 2018).…”
Section: Live Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations